Analysis of Swarm Satellite Magnetic Field Data Before the 2016 Ecuador (Mw = 7.8) Earthquake Based on Non-negative Matrix Factorization - Zhu, Kaiguang; Fan, Mengxuan; He, Xiaodan; Marchetti, Dedalo; Li, Kaiyan; Yu, Zining; Chi, Chengquan; Sun, Huihui; Cheng, Yuqi (Frontiers in Earth Science, 2021)
In this paper, based on Non-negative Matrix Factorization (NMF), we analyzed the ionosphere magnetic field data of Swarm Alpha satellite before the 2016 (Mw=7.8) Ecuador earthquake (April 16, 0.35°N, 79.93°W), including whole the data collected under quiet and disturbed geomagnetic conditions. The data of each track were decomposed into basis features and their corresponding weights. We found that the energy and entropy for one of the weight components were more concentrated inside the earthquake-sensitive area, which meant that this weight component was more likely to reflect the activity inside the earthquake-sensitive area. We focused on this weight component and used 5 times the Root Mean Square (RMS) to extract the anomalies. We found that for this weight component, the cumulative number of tracks, which had anomalies inside the earthquake-sensitive area, showed accelerated growth before the Ecuador earthquake and recovered to linear growth after the earthquake. To verify that the accelerated cumulative anomaly was possibly associated with the earthquake, we excluded the influence of the geomagnetic activity and the plasma bubble. Through the random earthquake study and the low-seismicity period study, the accelerated cumulative anomaly was shown to not be obtained by chance. Moreover, we observed that the cumulative Benioff strain S, which reflected the lithosphere activity, had acceleration behavior similar to the accelerated cumulative anomaly of the ionosphere magnetic field, which suggested that the anomaly that we obtained was possibly associated with the Ecuador earthquake and can be described by one of the Lithosphere Atmosphere Ionosphere Coupling (LAIC) model.